Unveiling the silent threat: Investigating asymptomatic plasmodium infections in Gorgora, Ethiopia through microscopy and loop-mediated isothermal amplification. - Tena Cherkos; Adane Derso; Banchamlak Tegegne; Abebe Birhanu; Kassahun Cherkos; Zufan Yiheyis Abreham; Banchayehu Getnet; Tsedenya Gebeyehu; Mulat Yimer; Tegegne Eshetu; Wossenseged Lemma; Aberham Abere; et al. (PLoS ONE)
Background The asymptomatic carriers of the Plasmodium parasite represent a large hidden reservoir of Plasmodium species. These individuals can carry microscopically detectable levels and sub-microscopic levels of Plasmodium parasitemia. As a result, the use of clinical diagnostic methods, such as Rapid Diagnosis Tests (RDTs) and Giemsa microscopy leads to underestimation of the burden of asymptomatic malaria. Thus, the use of highly sensitive molecular methods such as loop-mediated isothermal amplification techniques (LAMP) helps to overcome these limitations and is crucial to reporting the true burden of the disease. Objective This study aimed to determine the prevalence of Asymptomatic Plasmodium infections (APIs), and evaluate light microscopy for the detection of APIs using the LAMP method as a reference in Gorgora, Western Dembia district, Northwest Ethiopia. Method A community-based cross-sectional survey was carried out from May 17 to June 30, 2023, among households located in particular kebeles at Gorgora. The study participants were chosen using a multi-stage sampling technique. One Hundred Fifteen households and one household member from each household were selected using systematic random and simple random sampling techniques, respectively. To gather sociodemographic data, semi-structured questionnaires were used. Capillary blood samples were obtained from each study participant and screened for Plasmodium species infections using a LAMP kit and light microscopy. The data were entered into Epi Data version 4.6 and exported to SPSS version 25 for analysis. Results The prevalence of APIs through light microscopy examination and LAMP analysis was 6.1% (95%CI: 2.5-12.1) and 11.3% (95%CI: 6.2-18.6) respectively. Using LAMP as a reference, the sensitivity and specificity of microscopy were 53.8% and 100% respectively. Microscopy examination missed six Plasmodium infections that were positive by LAMP analysis. A measure of agreement between LAMP and Microscopy was found to be 0.67(k = 0.67). Conclusions A significant proportion of APIs was found which likely act as a reservoir of transmission. This study also showed a significant number of APIs were missed by microscopy techniques. Thus, efforts to control and eliminate malaria should also consider these sub-microscopic infections.